Crystals and skulls at Villa Gyllenberg - Granbacka, Camilla (Approaching religion, 2021)
Review of The Path to Hidden Knowledge, art exhibition curated by Nina Kokkinen, 3.6.-11.10.2020 at Villa Gyllenberg, Helsinki.